Debusi'nin aile hukukuyla ilgili görüşlerinin hilaf ilmi açısından değerlendirilmesi - Kalça, Fatma Betül (My University, 2021)
Hicri IV. asırda Mâverâünnehir’de yaşamış fıkıh âlimlerinden olan Debûsî, hem usûl hem de fürû ilmindeki yetkinliğiyle tanınmıştır. el-Esrar adlı eseri Hanefî mezhebine mensup müellifin Şâfiî mezhebine de vukûfiyetinin geniş olduğunu okuyucuya göstermektedir. Bu çalışmada inceleme konusu edilen eser hilâf ilmine dairdir. Müellif, mensup olduğu mezhebi münazara usûlü ile savunmaktadır. Eserde delilleri ile ele alınan konular Hanefîler ve Şafiîler arasındaki ihtilaflı konulardır. Eserde Hanefîler ve Şâfiîlerin görüşleri mukayese etmekle yetinilmeyip; Mâlikî ve bazı mutlak müçtehitlerin görüşlerine de yer verilmiştir. Eserin, Kitabu’n-Nikâh bahsine dair seçtiğimiz meselelerin değerlendirilmesini içeren çalışma, giriş ve iki bölümden oluşmaktadır. Girişte hilâf ilmi, birinci bölümde Debûsî ve el-Esrâr adlı eseri hakkında bilgi verilmektedir. İkinci bölümde ise Nikâh bölümü, muhteva ve metot yönünden değerlendirilmektedir. Son kısımda Kitabu’n-Nikâh’tan seçilen örnekler üzerinden meseleler tahlil edilerek Debûsî’nin hükümleri temellendirme metodu ve mezhebini savunma yöntemi hakkında tahlillere yer verilmektedir.

Dabūsī, who was one of the leading scholars of the Transoxiana century in 4 A.H, was known for his competence in the principles of Islamic jurisprudence (Usūl) as well as in its branches (furū’). His work, al-Asrar, shows the reader that although the author followed the Hanafi school of law, he put forward his understanding of the Shafi’i school of law. In this work, the subject of study is about the juristic disagreements (ʿilm al-khilāf). The author defends the denomination (madhhab) of which he is a member with the method of discussion. The issues discussed in the work with the evidence are controversial issues between Hanafis and Shafi'is. The author does not only compare the views of the Hanafis and the Shafi’is but he also sometimes defends his madhhab against Mâlikis and some absolute mujtahids (mujtahid muṭlaq). This study, which includes the evaluation of the matters regarding the Chapter of Marriage (kitab al-Nikâh), consists of an introduction and two sections. In the introduction, juristic disagreements are addressed and background information is given about Dabūsī and his work, al-Asrar, in the first section. In the last section, the component from the chapter of Marriage is evaluated in terms of its contents and method. By analyzing the sections chosen as an example from the Chapter of Marriage, analyses were made regarding Dabūsī’s proofing method and the way in which he defends his madhhab.
Keywords: al-Asrar; Debûsî; el-Esrar; Hilâf; Islamic law; İslam hukuku; Khilâf; Merriage; Nikâh Dabūsī